2010
DOI: 10.1159/000310350
|View full text |Cite
|
Sign up to set email alerts
|

Utilization Patterns of Ambulatory Medical Care before and after the Diagnosis of Dementia in Germany – Results of a Case-Control Study

Abstract: Aims: To analyze how the diagnosis of dementia changes the utilization of the ambulatory medical care services in the German statutory health insurance. Methods: In this case-control study, claims data of 1,848 insurants aged ≧65 years with incident dementia and 7,392 matched controls were compared regarding their utilization of ambulatory medical care services. Results: We found an increase in the utilization of ambulatory medical care services by demented patients of 50% in the year before and of 40% in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
45
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 29 publications
12
45
1
6
Order By: Relevance
“…The higher rates of primary care resource utilisation are evident in the AD cohort relative to GOA control patients as much as 3 years prior to AD diagnosis, with a sharp increase in the AD cohort immediately preceding the AD diagnosis that is maintained in the one year following diagnosis. This is the first study to report such a finding in the UK, and is consistent with results of other studies [13-15]. In Albert et al , the burden was measured by health care expenditures [13], while Ramakers et al and Eisele et al both used primary care consultation rates as a measure of health care burden [14,15].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The higher rates of primary care resource utilisation are evident in the AD cohort relative to GOA control patients as much as 3 years prior to AD diagnosis, with a sharp increase in the AD cohort immediately preceding the AD diagnosis that is maintained in the one year following diagnosis. This is the first study to report such a finding in the UK, and is consistent with results of other studies [13-15]. In Albert et al , the burden was measured by health care expenditures [13], while Ramakers et al and Eisele et al both used primary care consultation rates as a measure of health care burden [14,15].…”
Section: Discussionsupporting
confidence: 82%
“…Studies in the United States (US) [13], the Netherlands [14], and Germany [15] found that the number of primary care/ambulatory care consultations (or the cost of that care) increased prior to diagnosis and remained high immediately following diagnosis. Other studies in Denmark [11], the US [16], and France [17] found varying or even no differences in primary care resource utilisation in comparisons among patients with AD with differing degrees of impairment, and versus non-AD dementia or control cohorts without dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Sie werden in dieser Studie als Nervenärzte zusammengefasst. Weitere methodische Einzelheiten finden sich in den früheren Veröffentlichungen [10,12,13]. Die Analysen wurden mit SPSS 16, SAS (Version 9.2) und R (Version 2.11.1) durchgeführt.…”
unclassified
“…The medical data we used consisted of information on the physician who diagnosed the case, a history of the prescription antidementia drugs the patient was taking, and each patient's history of cardiovascular comorbidities, including diabetes mellitus, cerebrovascular diseases, hypertension, ischemic heart diseases, atrial fibrillation, and hypercholesterolemia (Eisele et al 2010;Kwok et al 2011;Ziegler 2011). We differentiated between four possible combinations of diagnosing physicians: 1. the patient's dementia was diagnosed by the GP only; 2. the dementia was diagnosed by an NP only; 3. the patient's GP and an NP both diagnosed the dementia in the same quarter; and 4.…”
Section: Medical and Demographic Variablesmentioning
confidence: 99%
“…Nevertheless, the majority of people, and especially the elderly, tend to consult their general practitioner (GP) first. Self-referrals to specialists such as neurologists or psychiatrists in suspected cases of dementia are possible, but patients are most often referred to these specialists by their GP (Eisele et al 2010).…”
Section: Introductionmentioning
confidence: 99%